2019
DOI: 10.1155/2019/6937837
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect ofLactobacillus plantarumFL75 andLeuconostoc mesenteroidesFL14againstFoodborne Pathogens in Artificially Contaminated Fermented Tomato Juices

Abstract: Tomatoes and tomato based-foods contain beneficial microorganisms and various organic acids that have important nutritional values for human. The objective of this study was to access the physiochemical properties of fermented tomatoes juices and to evaluate the competitiveness of lactic acid bacteria (LAB) against Listeria monocytogenes, Listeria innocua, and Salmonella spp., in artificially contaminated tomato juice. Microbial counting (LAB, fungi Salmonella spp., and Listeria spp.) was performed after ferme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…ZA3 had strong antimicrobial activity after excluding the effects of hydrogen peroxide by proteinase K and eliminating hydrogen peroxide from the cell-free culture supernatants; however, all activities disappeared completely when the cell-free supernatant was treated with neutralizing pH, which indicated that the antimicrobial activity may be attributed to the production of organic acids. Similarly, as one of the antimicrobial compounds, Tirloni et al [ 29 ] and Bah et al [ 30 ] proposed organic acids can significantly inhibit the growth of pathogenic bacteria. Silva et al [ 31 ] reported L. lactis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…ZA3 had strong antimicrobial activity after excluding the effects of hydrogen peroxide by proteinase K and eliminating hydrogen peroxide from the cell-free culture supernatants; however, all activities disappeared completely when the cell-free supernatant was treated with neutralizing pH, which indicated that the antimicrobial activity may be attributed to the production of organic acids. Similarly, as one of the antimicrobial compounds, Tirloni et al [ 29 ] and Bah et al [ 30 ] proposed organic acids can significantly inhibit the growth of pathogenic bacteria. Silva et al [ 31 ] reported L. lactis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…to inhibit the growth of pathogenic bacteria has already been demonstrated [31] [36] [37] [38]. Many studies have focused on the inhibition of pathogens by targeting bacteriocins.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely used for lactic acid production in food-grade applications. Recently, this bacterium has been recognized as a potential starter for tomato fermented juice products [24]. USFDA has approved the carbohydrate molecules produced from L. mesenteroides as safe substances (https ://www.fda.gov).…”
Section: Microbial Transformation Of Sweet Sorghum Juicementioning
confidence: 99%